Determination Of Sodium Nitrite in Dumplings Available in Online Shops Using Ultraviolet-Visible Spectrophotometry - Mulyaningsih, Listiana Neli; Putri, Saskia Anugrah; Muhaimin, Muhaimin; Kuntari, Kuntari (Walisongo Journal of Chemistry, 2024)
This research aims to determine the sodium nitrite content in dumplings in online stores based on differences in storage. The method used in this research is UV-Vis spectrophotometry with a maximum wavelength of 540 nm. The samples obtained from the online shop were two with different brands and were given the codes MT and CD. Samples in closed packaging that are still sealed are categorised as fresh samples and then tested for sodium nitrite content in the sample. Then, the remaining fresh samples were tested after being stored for 24 hours. The research results showed that the sodium nitrite content in fresh samples of different brands had different levels. Respectively, sodium nitrite levels with codes MT and CD were obtained at 9,890 mg/Kg and 15,545 mg/Kg. Samples that had undergone a 24-hour storage process with the MT and CD brands obtained 6,862 mg/Kg sodium nitrite contents and 13,209 mg/Kg. The sodium nitrite content in samples from different brands is still below the requirements set by the National Agency of Drug and Food Control of the Republic of Indonesia Regulation No. 11 of 2019 concerning food additives, namely 30 mg/Kg. This means that the sample is still categorised as suitable for consumption by the public. Fresh sample precision as %RPD for MT and CD brands is 7.030% and 6.954%. Meanwhile, sample precision after storage for the MT and CD brands was 8.382% and 1.921%, respectively. Thus, the precision in this test is declared to meet the acceptance requirements of 10%. The estimated uncertainty of the test for determining sodium nitrite levels in dumpling samples meets the acceptance requirements of 30% levels.